Cost-effectiveness of tailored print communication, telephone motivational interviewing, and a combination of the two: results of an economic evaluation alongside the Vitalum randomized controlled trial - van Keulen Hilde M; Bosmans Judith E; van Tulder Maurits W; Severens Johan L; de Vries Hein; Brug Johannes; Mesters Ilse (BMC, 2010)
Abstract Background The aim of the present study was to evaluate the cost-effectiveness of tailored print communication (TPC), telephone motivational interviewing (TMI), a combination of the two, and no intervention on two outcomes in adults aged 45 to 70, half of them having hypertension: increasing the number of public health guidelines met for three behaviors (physical activity and fruit and vegetable consumption), and impact on quality adjusted life years (QALYs). Methods Participants (n = 1,629) from 23 Dutch general practices were randomized into one of four groups, which received 4 TPCs, 4 TMIs, 2 of each (combined), or no intervention (control), respectively. The self-reported outcomes, measured at baseline and 73 weeks follow-up (7 months after the last intervention component), were difference in total number of guidelines met at follow-up compared to baseline, and number of QALYs experienced over 73 weeks. The costs of implementing the intervention were estimated using a bottom-up approach. Results At 73 weeks follow-up participants showed increased adherence with 0.62 (TPC), 0.40 (TMI), 0.50 (combined), and 0.26 (control) guidelines compared to baseline, and experienced 1.09, 1.08, 1.08, and 1.07 QALYs, respectively. The costs for the control group were considered to be zero. TMI was more expensive (€107 per person) than both the combined intervention (€80) and TPC (€57). The control condition was most cost-effective for lower ceiling ratios, while TPC had the highest probability of being most cost-effective for higher ceiling ratios (more than €160 per additional guideline met, and €2,851 for each individual QALY). Conclusions For low society's willingness to pay, the control group was most cost-effective for the number of QALYs experienced over 73 weeks. This also applied to the increase in the number of guidelines met at lower ceiling ratios, whereas at higher ceiling ratios, TPC had a higher probability of being more cost-effective than the TMI, combined or control conditions. This also seemed to apply for QALYs experienced over 73 weeks. More research is needed on the long-term efficacy of both TPC and TMI, as well as on how to increase their cost-effectiveness. Trial registration Dutch Trial Register NTR1068